Market Reaction to Mandatory IFRS Adoption: Evidence from Poland - Karol Marek Klimczak (Journal of Accounting and Management Information Systems (JAMIS), 2011)
This article analyses the effects of mandatory International Financial Reporting Standards adoption in Poland. Our aim is to determine how market participants reacted to the new accounting standards on the year of the adoption and whether their behavior changed afterwards. We examine abnormal returns around annual consolidated report publication, and the value relevance of earnings. Event studies show that annual report publication does not produce unexpected information either before, on, or after the adoption. Value relevance estimations produce consistent earnings coefficients for the unexpected earnings model for adopters and non-adopters. Interestingly, IFRS adopters are valued higher before the adoption, but not afterwards. The paper contributes a comprehensive methodology for market reaction studies and offers a range of possible extensions.
Keywords: M41; 650; IFRS; event study; value relevance; accounting regulation